Polarizing film with adhesive layer, image display panel and image display device

By using low molecular weight lithium ions as ionic compounds in the polarizing film with adhesive layer and combining (meth)acrylic polymers, the problems of electrostatic unevenness and special-shaped cracks in the prior art are solved, and better anti-static properties and optical reliability are achieved.

CN119644494APending Publication Date: 2025-03-18NITTO DENKO CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411979968.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2019-09-30
Filing Date
2019-10-30
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

When used in the embedded liquid crystal panel, the conventional polarizing film with an adhesive layer cannot sufficiently suppress the occurrence of electrostatic unevenness and special-shaped cracks, especially in the adhesive layer containing ionic compounds, the special-shaped cracks are prone to deterioration.

Method used

A polarizing film with an adhesive layer having a special-shaped portion other than a rectangle is used, and the adhesive layer consists of an ionic compound having a molecular weight of 210 or less of the cationic component. Lithium ions are preferably used, and the amount of ionic compound is reduced in the adhesive layer to suppress the generation of electrostatic unevenness and special-shaped cracks.

Benefits of technology

It effectively suppresses the generation of electrostatic unevenness and special-shaped cracks in the embedded liquid crystal panel, and improves the anti-static performance and optical reliability of the polarizing film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119644494A_ABST
    Figure CN119644494A_ABST
Patent Text Reader

Abstract

The present invention relates to a polarizing film with an adhesive layer, comprising a polarizing film and an adhesive layer, the polarizing film comprising a polarizer and a protective film provided on one or both surfaces of the polarizer, the polarizing film with the adhesive layer having a profiled section other than a rectangle, the pressure-sensitive adhesive layer is formed from a pressure-sensitive adhesive composition containing (A) a (meth) acrylic polymer and (B) an ionic compound having a cationic component molecular weight of 210 or less. The polarizing film with the adhesive layer and having the irregularly-shaped part can suppress generation of irregularly-shaped cracks and can suppress static unevenness even when applied to an in-cell liquid crystal panel.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present application is a divisional application of an application filed on October 30, 2019, with application number 201980090169.1 and invention name “Polarizing film with adhesive layer, image display panel and image display device”. Technical Field

[0002] The present invention relates to a polarizing film with an adhesive layer having a non-rectangular irregular shape. The present invention also relates to an image display panel and an image display device using the polarizing film with an adhesive layer. Background Art

[0003] Image display panels, such as liquid crystal panels used in liquid crystal display devices, are usually laminated with polarizing films on both sides of a liquid crystal cell through an adhesive layer, and the liquid crystal cell is formed by a liquid crystal layer disposed between a pair of transparent substrates. On the other hand, when manufacturing the image display panel, when the polarizing film with the adhesive layer is attached to the liquid crystal cell, the release film is peeled off from the adhesive layer of the polarizing film with the adhesive layer, and static electricity is generated due to the peeling of the release film. The static electricity generated in this way, for example, affects the orientation of the liquid crystal layer inside the liquid crystal display panel, thereby causing defects. The generation of static electricity can be suppressed, for example, by forming an antistatic layer (conductive layer) on the outer surface of the polarizing film.

[0004] For example, in Patent Document 1, in order to reduce the occurrence of display defects and malfunctions in a liquid crystal display device with a touch sensor function, it is proposed to arrange a thin film having a surface resistance of 1.0×10 9 ~1.0×10 11 It is also known that the generation of static electricity can be suppressed by adding an ionic compound as an antistatic agent to the adhesive layer.

[0005] On the other hand, in recent years, there has been an increase in the number of irregular-shaped built-in liquid crystal display devices in smart phones and car navigation systems, and as for polarizing films, irregular-shaped polarizing films are also used in conjunction with the display devices. Patent document 2 discloses a method of manufacturing a polarizing film having an irregular shape other than a rectangular shape by processing a polarizing film. Patent document 3 proposes to improve the irregular punching property of the polarizing film and the crack durability of the irregular-shaped polarizing film after punching after a heating cycle test by including irregular-shaped inorganic particles in a transparent protective film for the polarizing film.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2013-105154

[0009] Patent Document 2: Japanese Patent Application Publication No. 2017-151191

[0010] Patent Document 3: Japanese Patent Application Publication No. 2017-097111 Summary of the invention

[0011] Problems to be solved by the invention

[0012] According to the polarizing film with an antistatic layer described in Patent Document 1, the generation of static electricity can be suppressed. However, even a polarizing film with an adhesive layer provided with an antistatic layer or an adhesive layer containing an ionic compound cannot fully suppress static unevenness. In addition, for a polarizing film with an adhesive layer having an irregular shape, even a polarizing film with an adhesive layer provided with an antistatic layer or an adhesive layer containing an ionic compound cannot fully suppress the irregular cracks generated in the irregular portion. In particular, when a polarizing film with an adhesive layer containing an ionic compound in the adhesive layer and having an irregular portion is applied to an embedded liquid crystal panel, it is known that a large amount of ionic compounds need to be added to the above-mentioned adhesive layer, as a result of which the irregular cracks generated in the irregular portion are aggravated.

[0013] The object of the present invention is to provide a polarizing film with an adhesive layer having an antistatic function, which is a polarizing film with an adhesive layer having a shaped portion. Even when the polarizing film is applied to an embedded liquid crystal panel, it can suppress the occurrence of shaped cracks and can suppress static unevenness.

[0014] Another object of the present invention is to provide an image display panel and an image display device using the above-mentioned pressure-sensitive adhesive layer-attached polarizing film.

[0015] Solutions to the problem

[0016] The present inventors have conducted intensive studies to solve the above-mentioned problems and, as a result, have found the following pressure-sensitive adhesive layer-attached polarizing film, thereby completing the present invention.

[0017] That is, the present invention relates to a polarizing film with an adhesive layer, which comprises a polarizing film and an adhesive layer, wherein the polarizing film comprises a polarizer and a protective film provided on one or both surfaces of the polarizer.

[0018] The polarizing film with an adhesive layer has a non-rectangular shaped portion.

[0019] The pressure-sensitive adhesive layer is formed from a pressure-sensitive adhesive composition containing a (meth)acrylic polymer (A) and an ionic compound (B) having a molecular weight of 210 or less as a cationic component.

[0020] In the pressure-sensitive adhesive layer-attached polarizing film, the cationic component is preferably a lithium ion.

[0021] The pressure-sensitive adhesive layer-attached polarizing film preferably contains 0.1 to 13 parts by weight of the ionic compound (B) based on 100 parts by weight of the (meth)acrylic polymer (A).

[0022] In the pressure-sensitive adhesive layer-attached polarizing film, it is preferable that the protective film is any one selected from a cellulose resin film and a (meth)acrylic resin film. In addition, it is preferable that the thickness of the polarizer in the polarizing film is 10 μm or less.

[0023] The pressure-sensitive adhesive layer-attached polarizing film may be a single-side protective polarizing film having a polarizer and a protective film provided only on one side of the polarizer. The single-side protective polarizing film preferably has the pressure-sensitive adhesive layer on the other side of the polarizer.

[0024] The single-side protective polarizing film may have the adhesive layer on the other side of the polarizer via a transparent layer having a thickness of 10 μm or less, the transparent layer being directly formed on the polarizer. As the transparent layer, a cured product of a forming material containing a urethane prepolymer, which is a reaction product of an isocyanate compound and a polyol, may be used.

[0025] In the pressure-sensitive adhesive layer-attached polarizing film, the pressure-sensitive adhesive layer preferably has a creep value at 85° C. of 120 μm or less.

[0026] The present invention also relates to an image display panel having the above-mentioned polarizing film with an adhesive layer. The above-mentioned image display panel can also be applied to an image display panel having an adhesive layer of the polarizing film with an adhesive layer attached to a liquid crystal cell with a built-in touch sensor function having a liquid crystal layer and a touch sensor portion.

[0027] In addition, the present invention relates to an image display device including the above-mentioned image display panel.

[0028] Effects of the Invention

[0029] The polarizing film with an adhesive layer of the present invention contains an ionic compound in the adhesive layer, and the antistatic performance can be improved by the adhesive layer. In addition, it is known that for the above-mentioned ionic compound, the smaller the molecular weight of the cationic component, the smaller the adverse effect on the irregular cracks, and therefore, an ionic compound with a molecular weight of the cationic component of 210 or less is used. In particular, it is known that when a lithium salt is used as the cationic component of the ionic compound, the effect of suppressing irregular cracks is excellent. In addition, it is known that the smaller the molecular weight of the above-mentioned cationic component, the more preferred it is from the perspective of suppressing static unevenness.

[0030] The polarizing film with an adhesive layer of the present invention has a non-rectangular shaped portion, but as described above, the polarizing film with an adhesive layer of the present invention contains an ionic compound with a small molecular weight of a cationic component in the adhesive layer as an ionic compound. Therefore, even if the amount of the ionic compound is reduced, the antistatic function of the adhesive layer can suppress static unevenness when the polarizing film with an adhesive layer is applied to an embedded liquid crystal panel. In addition, since the amount of the ionic compound can be reduced, the generation of shaped cracks can be suppressed.

[0031] It is also known that the effect of suppressing irregular cracks is advantageous when a single-side protected polarizing film having a protective film only on one side of the polarizer is used as the polarizing film. A single-side protected polarizing film is also advantageous from the viewpoint of thinning and cost reduction.

[0032] On the other hand, it is also known that when a single-side protective polarizing film is used as a polarizing film, there is a concern that the antistatic function of the adhesive layer will be reduced due to the segregation of the ionic compound contained in the adhesive layer to the polarizer in a humid environment. In this way, when a single-side protective polarizing film is used, the adhesive layer is provided on the polarizer via a transparent layer, and the ionic compound of the adhesive layer does not directly affect the polarizer. This can suppress the discoloration of the end of the polarizer in a humid environment.

[0033] As described above, the polarizing film with an adhesive layer according to the present invention can suppress the degradation of the optical reliability of the polarizer even when a single-side protective polarizing film is used, and can provide a polarizing film with an adhesive layer that is thin, has good optical reliability, and has excellent antistatic properties for a long time. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a cross-sectional view showing an example of the pressure-sensitive adhesive layer-attached polarizing film of the present invention.

[0035] Figure 2 This is a cross-sectional view showing an example of the pressure-sensitive adhesive layer-attached polarizing film of the present invention.

[0036] Figure 3 This is a cross-sectional view showing an example of the pressure-sensitive adhesive layer-attached polarizing film of the present invention.

[0037] Figure 4 It is a plan view showing an example of a non-rectangular irregular portion of the pressure-sensitive adhesive layer-attached polarizing film of the present invention.

[0038] Figure 5 It is a top view showing a polarizing film with a pressure-sensitive adhesive layer having a deformed portion according to an embodiment of the present invention.

[0039] Figure 6This is a cross-sectional view showing an example of a liquid crystal panel with a touch sensor function using the pressure-sensitive adhesive layer-attached polarizing film of the present invention.

[0040] Figure 7 This is a cross-sectional view showing an example of a liquid crystal panel with a touch sensor function using the pressure-sensitive adhesive layer-attached polarizing film of the present invention.

[0041] Figure 8 This is a cross-sectional view showing an example of a liquid crystal panel with a touch sensor function using the pressure-sensitive adhesive layer-attached polarizing film of the present invention.

[0042] Explanation of symbols

[0043] 1 Polarizing film with adhesive layer

[0044] 11. Single-side protective polarizing film

[0045] a Polarizer

[0046] b. Protective film

[0047] c Transparent layer

[0048] 21 Adhesive layer

[0049] 2 Notch (special-shaped part)

[0050] W1 Notch length

[0051] D Maximum depth of the notch from W1

[0052] θ1 Angle between two straight lines

[0053] R1 Curvature radius of the curve

[0054] 11, 12 First and second polarizing films

[0055] 21, 22 first and second adhesive layers

[0056] 3 Liquid crystal layer

[0057] 41, 42 first and second transparent substrates

[0058] 5 Touch sensor section

[0059] 6 Driving electrode and sensor part

[0060] 7. Driving Electrode

[0061] C Liquid crystal unit DETAILED DESCRIPTION

[0062] The pressure-sensitive adhesive layer-attached polarizing film of the present invention is shown, for example, in Figure 1 .like Figure 1As shown, the pressure-sensitive adhesive layer-attached polarizing film 1 includes a polarizing film 11 and a pressure-sensitive adhesive layer 21 . Figure 2 A single-side protective polarizing film 11A having a protective film b on only one side of the polarizer a is used as Figure 1 In the case of the polarizing film 11, in the above-mentioned single-sided protective polarizing film 11A, the other side of the side of the above-mentioned polarizer a that does not have the protective film b has the above-mentioned adhesive layer 21. It should be noted that, although not shown in the figure, as a single-sided protective polarizing film A2 having a protective film b only on one side of the above-mentioned polarizer a, a laminate having a polarizer a / protective film b / adhesive layer 21 in this order can also be used. Figure 3 In the case where the above-mentioned single-side protective polarizing film 11A is used, a transparent layer d is further provided on the other side of the above-mentioned polarizer a. Figure 3 In the embodiment, the transparent layer c and the adhesive layer 21 are sequentially provided on the one-side protective polarizing film 11A. From the viewpoint of suppressing the increase of the moisture content of the polarizer in a high temperature and high humidity environment, it is preferable that the transparent layer c is directly provided on the polarizer a.

[0063] <Special Shape Department>

[0064] Moreover, the pressure-sensitive adhesive layer-attached polarizing film of the present invention has a non-rectangular irregular portion. Figure 4 This is a top view of an example of a polarizing film with an adhesive layer having a non-rectangular shaped portion. The non-rectangular shape is not particularly limited, and can be any shape according to the purpose, function, and design of the polarizing film with an adhesive layer. Examples of the non-rectangular shaped portion include a notch or a through hole in the rectangle.

[0065] The notch is provided at the outer edge of the polarizing film with the adhesive layer. When a plurality of notches are provided, they may be of the same shape or of different shapes. Two or more notches may be provided on one side, or one or more notches may be provided on each of the two sides. In addition, the notch may be provided at one of the four corners of the outer edges of the rectangle, or at two or more of them. It should be noted that the corners of the outer edges where the notches are not provided may be square or circular. The notches may be composed of straight lines, curves, or a combination thereof. Figure 4 This is an example of a polarizing film 1 with a pressure-sensitive adhesive layer having a non-uniform shape, and notches 2 having different shapes are provided on both short sides of the rectangle.

[0066] The length of the side W1 of the notch is appropriately adjusted according to the application of the polarizing film. For example, W1 is preferably adjusted within a range of about 2 to 100 mm. In addition, the maximum depth D of the notch 2 from the side W1 is preferably adjusted within a range of about 2 to 100 mm.

[0067] exist Figure 4 In the figure, the angle θ1 formed by the two straight lines constituting the shape of the notch 2 is 90°, and the angle θ1 is greater than 90° and less than 180°, preferably greater than 90° and less than 135°. When the angle θ1 is outside the above range, in a severe environment of thermal shock, the stress due to expansion / contraction is concentrated on the portion 4 where the two straight lines intersect, and cracks are likely to occur in the portion 4.

[0068] In addition, Figure 4 In the embodiment of the present invention, the curve constituting the shape of the notch 2 is described, and the curvature radius R1 of the curve is 0.2 mm or more, preferably 1 mm or more, more preferably 2 mm or more, further preferably 3 mm or more, and further preferably 5 mm or more. When the curvature radius R1 is less than 0.2 mm, in a severe environment of thermal shock, the stress due to expansion / contraction is concentrated on the curve portion, and cracks are easily generated in the curve portion.

[0069] The through hole is arranged inside the plane of the polarizing film with the adhesive layer. When a plurality of through holes are arranged inside the plane of the polarizing film with the adhesive layer, they may be of the same shape or of different shapes. The through hole is composed of a straight line, a curve, or a combination thereof. Examples of the shape of the through hole include a circle, an ellipse (a shape with one axis of symmetry, a shape with two axes of symmetry), a rounded rectangle, a quadrilateral (square, rectangle), and a polygon with five or more sides.

[0070] Examples of methods for forming the irregularly shaped portion include punching, end milling, and laser processing. The irregularly shaped portion is usually formed by laminating each layer and then performing the above processing.

[0071] <Polarizing film with adhesive layer>

[0072] First, the respective members constituting the pressure-sensitive adhesive layer-attached polarizing film of the present invention will be described. The polarizing film used includes a polarizer and a protective film provided on one or both surfaces of the polarizer.

[0073] The polarizer is not particularly limited, and various polarizers can be used. Examples of the polarizer include films obtained by adsorbing dichroic substances such as iodine and dichroic dyes on hydrophilic polymer films such as polyvinyl alcohol films, partially formalized polyvinyl alcohol films, and partially saponified films of ethylene-vinyl acetate copolymers and then uniaxially stretching them, polyolefin oriented films such as dehydrated products of polyvinyl alcohol and dehydrochlorinated products of polyvinyl chloride, etc. Among these, polarizers formed of dichroic substances such as polyvinyl alcohol films and iodine are preferred. The thickness of these polarizers is not particularly limited, and is generally about 80 μm or less.

[0074] In addition, as a polarizer, a thin polarizer with a thickness of 10 μm or less can be used. From the perspective of thinning, the thickness is preferably 1 to 7 μm. Such a thin polarizer has less uneven thickness, excellent visibility, and less dimensional change, so it has excellent durability, and the thickness of the polarizing film can also be thinned, which is preferred in this respect.

[0075] As the material constituting the protective film, for example, a thermoplastic resin having excellent transparency, mechanical strength, thermal stability, moisture barrier property, isotropy, etc. can be used. Specific examples of such thermoplastic resins include: cellulose resins such as cellulose triacetate, polyester resins, polyethersulfone resins, polysulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins, (meth)acrylic resins, cyclic polyolefin resins (such as norbornene resins), polyarylate resins, polystyrene resins, polyvinyl alcohol resins, and mixtures thereof. It should be noted that a protective film can usually be attached to one side of the polarizer through an adhesive layer, and a thermosetting resin or ultraviolet curing resin such as (meth)acrylic, urethane, acrylic urethane, epoxy, silicone, etc. can be used as a protective film on the other side.

[0076] As the material of the above-mentioned protective film (transparent protective film), cellulose resin and (meth) acrylic resin are preferred because they can control the variation of the surface resistance value of the adhesive layer to be smaller. As the (meth) acrylic resin, it is preferred to use a (meth) acrylic resin having a lactam ring structure. It should be noted that as the (meth) acrylic resin having a lactam ring structure, the (meth) acrylic resin having a lactam ring structure described in Japanese Patent Publication No. 2000-230016, Japanese Patent Publication No. 2001-151814, Japanese Patent Publication No. 2002-120326, Japanese Patent Publication No. 2002-254544, Japanese Patent Publication No. 2005-146084, etc. can be cited. In particular, from the perspective of effectively suppressing the irregular cracks and polarizer cracks that become problems in the single-sided protective polarizing film, cellulose resin is preferred over (meth) acrylic resin.

[0077] As the above-mentioned protective film, a phase difference film, a brightness enhancement film, a diffusion film, etc. can also be used. As the phase difference film, a phase difference film having a front phase difference of more than 40nm and / or a phase difference in the thickness direction of more than 80nm can be listed. The front phase difference is usually controlled in the range of 40 to 200nm, and the thickness direction phase difference is usually controlled in the range of 80 to 300nm. In the case of using a phase difference film as a protective film, the phase difference film also functions as a polarizer protective film, and therefore, thinning can be achieved.

[0078] A functional layer such as a hard coat layer, an antireflection layer, an antisticking layer, a diffusion layer, an antiglare layer, etc. may be provided on the side of the protective film to which the polarizer is not bonded.

[0079] The protective film and the polarizer can be laminated via an interlayer such as an adhesive layer, a bonding agent layer, or an undercoat layer. In this case, it is preferred to laminate the two in an air-gap-free manner using an interlayer. The protective film and the polarizer are preferably laminated via an adhesive layer. There are no particular restrictions on the adhesive used in laminating the polarizer and the protective film as long as it is optically transparent. Various forms of adhesives such as water-based, solvent-based, hot-melt, free radical-curing, and cationic-curing can be used, preferably water-based adhesives or free radical-curing adhesives.

[0080] <Adhesive layer>

[0081] The pressure-sensitive adhesive layer is formed from a pressure-sensitive adhesive composition containing a (meth)acrylic polymer (A) and an ionic compound (B).

[0082] The (meth)acrylic polymer (A) contains as a main component an alkyl (meth)acrylate as a monomer unit. (Meth)acrylate refers to acrylate and / or methacrylate, and has the same meaning as (meth) in the present invention.

[0083] As the (meth)acrylic acid alkyl ester constituting the main skeleton of the (meth)acrylic polymer (A), there can be exemplified linear or branched (meth)acrylic acid alkyl esters having an alkyl carbon number of 1 to 18. For example, as the above-mentioned alkyl group, there can be cited methyl, ethyl, propyl, isopropyl, butyl, isobutyl, pentyl, hexyl, cyclohexyl, heptyl, 2-ethylhexyl, isooctyl, nonyl, decyl, isodecyl, dodecyl, isotetradecyl, lauryl, tridecyl, pentadecyl, hexadecyl, heptadecyl, octadecyl, etc. These can be used alone or in combination. The average carbon number of these alkyl groups is preferably 3 to 9.

[0084] In terms of monomer units, the weight ratio of the alkyl (meth)acrylate is preferably 70% by weight or more in the weight ratio of all the constituent monomers (100% by weight) constituting the (meth)acrylic polymer (A). The weight ratio of the alkyl (meth)acrylate can be regarded as the remainder of other copolymerized monomers. It is preferable to set the weight ratio of the alkyl (meth)acrylate to the above range in terms of ensuring adhesion.

[0085] In order to improve adhesion and heat resistance, in addition to the monomer units of the above-mentioned alkyl (meth)acrylate, one or more comonomers having a polymerizable functional group having an unsaturated double bond such as a (meth)acryloyl group or a vinyl group may be introduced into the above-mentioned (meth)acrylic polymer (A) by copolymerization.

[0086] Examples of the comonomer include functional group-containing monomers such as carboxyl group-containing monomers, hydroxyl group-containing monomers, and amide group-containing monomers.

[0087] The carboxyl group-containing monomer is a compound containing a carbonyl group in its structure and containing polymerizable unsaturated double bonds such as (meth)acryloyl and vinyl groups. Specific examples of carboxyl group-containing monomers include (meth)acrylic acid, (meth)carboxyethyl acrylate, (meth)carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, etc. Among the above-mentioned carboxyl group-containing monomers, acrylic acid is preferred from the viewpoints of copolymerizability, price and adhesive properties.

[0088] The hydroxyl-containing monomer is a compound containing a hydroxyl group in its structure and containing polymerizable unsaturated double bonds such as (meth)acryloyl and vinyl groups. Specific examples of hydroxyl-containing monomers include: 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate and other hydroxyalkyl (meth)acrylates, acrylate (4-hydroxymethylcyclohexyl)methyl, etc. Among the above-mentioned hydroxyl-containing monomers, 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate are preferred from the aspect of durability, and 4-hydroxybutyl (meth)acrylate is particularly preferred.

[0089] When the adhesive composition contains a crosslinking agent, the carboxyl-containing monomer and the hydroxyl-containing monomer become the reaction points with the crosslinking agent. Since the reactivity of the carboxyl-containing monomer and the hydroxyl-containing monomer with the intermolecular crosslinking agent is high, they are preferably used in order to improve the cohesiveness and heat resistance of the obtained adhesive layer. In addition, the carboxyl-containing monomer is preferred in terms of durability and reoperability, and the hydroxyl-containing monomer is preferred in terms of reoperability.

[0090] The above-mentioned weight ratio of the carboxyl group-containing monomer is preferably 10 weight % or less, more preferably 0.01 to 8 weight %, further preferably 0.05 to 6 weight %, and further preferably 0.1 to 5 weight %. It is preferred to set the weight ratio of the carboxyl group-containing monomer to 0.01 weight % or more in terms of durability. On the other hand, when it is greater than 10 weight %, it is not preferred from the perspective of reoperability.

[0091] The weight ratio of the hydroxyl-containing monomer is preferably 3% by weight or less, more preferably 0.01 to 3% by weight, further preferably 0.1 to 2% by weight, and further more preferably 0.2 to 2% by weight. From the perspective of crosslinking the adhesive layer, durability, and adhesive properties, the weight ratio of the hydroxyl-containing monomer is preferably set to 0.01% by weight or more. On the other hand, when it is greater than 3% by weight, it is not preferred from the perspective of durability.

[0092] The amide group-containing monomer is a compound containing an amide group in its structure and containing a polymerizable unsaturated double bond such as a (meth)acryloyl group and a vinyl group. Specific examples of the amide group-containing monomer include: acrylamide monomers such as (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-isopropylacrylamide, N-methyl(meth)acrylamide, N-butyl(meth)acrylamide, N-hexyl(meth)acrylamide, N-hydroxymethyl(meth)acrylamide, N-hydroxymethyl-N-propyl(meth)acrylamide, aminomethyl(meth)acrylamide, aminoethyl(meth)acrylamide, mercaptomethyl(meth)acrylamide, and mercaptoethyl(meth)acrylamide; N-acryloyl heterocyclic monomers such as N-(meth)acryloylmorpholine, N-(meth)acryloylpiperidine, and N-(meth)acryloylpyrrolidine; and N-vinyl lactam-containing monomers such as N-vinylpyrrolidone and N-vinyl-ε-caprolactam. The amide group-containing monomer is preferred in terms of suppressing the increase in surface resistance over time (especially in a humidified environment), satisfying durability, and further suppressing irregular cracks. In particular, among the amide group-containing monomers, the N-vinyl lactam-containing monomer is preferred in terms of suppressing the increase in surface resistance over time (especially in a humidified environment), satisfying durability for the transparent conductive layer (touch sensor layer), and suppressing irregular cracks.

[0093] When the weight ratio of the amide group-containing monomer increases, there is a tendency for the anchoring property to the optical film to decrease, and therefore, the weight ratio is preferably 10% by weight or less, and particularly preferably 5% by weight or less. From the viewpoint of suppressing the increase of the surface resistance value over time (especially in a humidified environment), the weight ratio of the amide group-containing monomer is preferably 0.1% by weight or more, and the weight ratio is preferably 0.3% by weight or more, and more preferably 0.5% by weight or more. Considering the relationship with the ionic compound (B) contained in the adhesive layer of the present invention, the amide group-containing monomer is suitable.

[0094] When an amide group is introduced into the side chain of the (meth)acrylic polymer (A) as the base polymer in the adhesive composition used for forming the adhesive layer, the presence of the amide group can suppress the surface resistance value of the adhesive layer adjusted by the coordination of the ionic compound (B) from changing and increasing even in a humidified environment, and it is preferred in terms of maintaining it within the range of a desired value. It is believed that the presence of the amide group introduced into the side chain of the (meth)acrylic polymer (A) as a functional group of a comonomer improves the compatibility of the (meth)acrylic polymer (A) and the ionic compound (B).

[0095] In addition, when there is an amide group introduced into the side chain of the (meth) acrylic polymer (A) as the base polymer in the adhesive layer, the durability to either glass or the transparent conductive layer (ITO layer, etc.) is good, and it is possible to suppress peeling, warping, etc. when attached to a liquid crystal panel. In addition, the durability can be satisfied even in a humidified environment (after a humidified reliability test).

[0096] In addition, as a comonomer, for example, an aromatic ring-containing (meth)acrylate can be used. An aromatic ring-containing (meth)acrylate is a compound containing an aromatic ring structure and a (meth)acryloyl group in its structure. Examples of the aromatic ring include a benzene ring, a naphthalene ring, and a biphenyl ring.

[0097] Specific examples of the aromatic ring-containing (meth)acrylate include benzyl (meth)acrylate, phenyl (meth)acrylate, o-phenylphenol (meth)acrylate, phenoxymethyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxypropyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, ethylene oxide-modified nonylphenol (meth)acrylate, ethylene oxide-modified cresol (meth)acrylate, phenol ethylene oxide-modified (meth)acrylate, 2-hydroxy (meth)acrylate, (Meth)acrylates having a benzene ring, such as -3-phenoxypropyl, methoxybenzyl (meth)acrylate, benzyl (meth)acrylate chloride, toluene (meth)acrylate, styrene (meth)acrylate; (meth)acrylates having a naphthalene ring, such as hydroxyethylated β-naphthol acrylate, 2-naphthylethyl (meth)acrylate, 2-naphthyloxyethyl acrylate, 2-(4-methoxy-1-naphthyloxy)ethyl (meth)acrylate; (meth)acrylates containing an aromatic ring, such as biphenyl (meth)acrylate, having a biphenyl ring.

[0098] As the aromatic ring-containing (meth)acrylate, benzyl (meth)acrylate and phenoxyethyl (meth)acrylate are preferred from the viewpoint of adhesive properties and durability, and phenoxyethyl (meth)acrylate is particularly preferred.

[0099] The weight ratio of the aromatic ring-containing (meth)acrylate is preferably 25% by weight or less, more preferably 3 to 25% by weight, further preferably 10 to 22% by weight, and further preferably 14 to 20% by weight. When the weight ratio of the aromatic ring-containing (meth)acrylate is 3% by weight or more, it is preferred in terms of suppressing uneven display. On the other hand, when it is greater than 25% by weight, the suppression of uneven display is insufficient, and there is a tendency for durability to decrease.

[0100] Specific examples of other copolymer monomers other than those mentioned above include anhydride group-containing monomers such as maleic anhydride and itaconic anhydride; caprolactone adducts of acrylic acid; sulfonic acid group-containing monomers such as allyl sulfonic acid, 2-(meth)acrylamide-2-methylpropanesulfonic acid, (meth)acrylamidepropanesulfonic acid, and (meth)acrylate sulfopropyl ester; phosphate group-containing monomers such as 2-hydroxyethylacryloyl phosphate, etc.

[0101] Examples of monomers for modification include: alkylaminoalkyl (meth)acrylates such as aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, and tert-butylaminoethyl (meth)acrylate; alkoxyalkyl (meth)acrylates such as methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate; N-(meth)acryloyloxymethylenesuccinimide, N-(meth)acryloyl-6-oxyhexam ... Succinimide monomers such as succinimide (acryloyl-8-oxyoctamethylene succinimide) and the like; maleimide monomers such as N-cyclohexylmaleimide, N-isopropylmaleimide, N-dodecylmaleimide, and N-phenylmaleimide; itaconimide monomers such as N-methylitaconimide, N-ethylitaconimide, N-butylitaconimide, N-octylitaconimide, N-2-ethylhexylitaconimide, N-cyclohexylitaconimide, and N-dodecylitaconimide.

[0102] In addition, as the modifying monomer, vinyl monomers such as vinyl acetate and vinyl propionate; cyanoacrylate monomers such as acrylonitrile and methacrylonitrile; epoxy group-containing (meth)acrylates such as glycidyl (meth)acrylate; glycol (meth)acrylates such as polyethylene glycol (meth)acrylate, polypropylene glycol (meth)acrylate, methoxyethylene glycol (meth)acrylate, methoxypolypropylene glycol (meth)acrylate; acrylate monomers such as tetrahydrofurfuryl (meth)acrylate, fluorine-containing (meth)acrylate, silicone (meth)acrylate, 2-methoxyethyl acrylate, etc. can also be used. In addition, isoprene, butadiene, isobutylene, vinyl ether, etc. can be cited.

[0103] In addition, as copolymerizable monomers other than the above, silane monomers containing silicon atoms can be cited. As silane monomers, for example, 3-acryloxypropyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, 4-vinylbutyltrimethoxysilane, 4-vinylbutyltriethoxysilane, 8-vinyloctyltrimethoxysilane, 8-vinyloctyltriethoxysilane, 10-methacryloxydecyltrimethoxysilane, 10-acryloxydecyltrimethoxysilane, 10-methacryloxydecyltriethoxysilane, 10-acryloxydecyltriethoxysilane, etc. can be cited.

[0104] As the comonomer, there may be used a polyfunctional monomer having two or more unsaturated double bonds such as (meth)acrylic acid or vinyl groups, such as an ester of (meth)acrylic acid and a polyol such as tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, bisphenol A diglycidyl ether di(meth)acrylate, neopentyl glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, caprolactone-modified dipentaerythritol hexa(meth)acrylate, and a polyester (meth)acrylate, epoxy (meth)acrylate, urethane (meth)acrylate, etc., in which two or more unsaturated double bonds such as (meth)acryloyl groups or vinyl groups are added to a skeleton of polyester, epoxy, urethane, etc. as the same functional groups as the monomer components.

[0105] The ratio of the other copolymerizable monomers in the (meth)acrylic polymer (A) is preferably about 0 to 10% by weight, more preferably about 0 to 7% by weight, and even more preferably about 0 to 5% by weight, based on the weight ratio of all monomers constituting the (meth)acrylic polymer (A) (100% by weight).

[0106] The weight average molecular weight of the (meth) acrylic polymer (A) of the present invention is generally preferably 1 million to 2.5 million. If durability, especially heat resistance, is taken into consideration, the weight average molecular weight is preferably 1.2 million to 2 million. When the weight average molecular weight is 1 million or more, it is preferred in terms of heat resistance. In addition, when the weight average molecular weight is greater than 2.5 million, there is a tendency for the adhesive to harden easily and peeling occurs easily. In addition, the weight average molecular weight (Mw) / number average molecular weight (Mn) representing the molecular weight distribution is preferably 1.8 or more and 10 or less, more preferably 1.8 to 7, and further preferably 1.8 to 5. When the molecular weight distribution (Mw / Mn) is greater than 10, it is not preferred in terms of durability. It should be noted that the weight average molecular weight and the molecular weight distribution (Mw / Mn) are determined by GPC (gel permeation chromatography) and calculated by polystyrene conversion.

[0107] Such (meth)acrylic polymer (A) can be produced by appropriately selecting known production methods such as solution polymerization, bulk polymerization, emulsion polymerization, various radical polymerizations, etc. The obtained (meth)acrylic polymer (A) may be any copolymer such as a random copolymer, a block copolymer, or a graft copolymer.

[0108] In solution polymerization, ethyl acetate, toluene, etc. are used as polymerization solvents. As a specific example of solution polymerization, the reaction is carried out under a stream of an inert gas such as nitrogen, with a polymerization initiator added, usually at about 50 to 70° C. for about 5 to 30 hours.

[0109] The polymerization initiator, chain transfer agent, emulsifier, etc. used in the free radical polymerization are not particularly limited and can be appropriately selected for use. In addition, the weight average molecular weight of the (meth)acrylic polymer (A) can be controlled by the amount of the polymerization initiator and chain transfer agent used and the reaction conditions, and the amount used can be appropriately adjusted according to the type of the polymerization initiator and chain transfer agent.

[0110] <Ionic compound (B)>

[0111] As the ionic compound (B) contained in the adhesive composition forming the adhesive layer of the present invention, an ionic compound having a molecular weight of 210 or less of the cationic component is used. From the viewpoint of suppressing the generation of irregular cracks, the molecular weight of the cationic component is more preferably 150 or less, further preferably 110 or less, further preferably 50 or less, and further preferably 10 or less. The larger the molecular weight of the cationic component, the more there is a tendency to hinder the entanglement of the (meth) acrylic polymers in the adhesive layer, thereby softening the physical properties of the adhesive layer. Therefore, the smaller the molecular weight, the less likely the physical properties of the adhesive layer are to become soft, and the more the generation of irregular cracks can be suppressed. In addition, the smaller the molecular weight of the cationic component, the easier it is to reduce the surface resistance value of the adhesive layer, which is also preferred from the perspective of suppressing static unevenness.

[0112] The above-mentioned ionic compound (B) can preferably use alkali metal salts and / or organic cation-anion salts. Alkali metal salts can use organic salts and inorganic salts of alkali metals. It should be noted that the "organic cation-anion salt" mentioned in the present invention refers to an organic salt whose cation component is composed of an organic substance, and the anion component can be an organic substance or an inorganic substance. "Organic cation-anion salt" is also called ionic liquid or ionic solid. By containing an ionic compound (B) in the above-mentioned adhesive layer, the surface resistance value of the adhesive layer can be reduced to suppress the generation of static electricity, and the light leakage (uneven charging) caused by the disorder of the orientation of the liquid crystal layer due to charging can be suppressed.

[0113] <Alkali metal salts>

[0114] Examples of the alkali metal ions constituting the cation component of the alkali metal salt include ions of lithium, sodium, potassium, etc. Among these alkali metal ions, lithium ions are preferred.

[0115] The anion component of the alkali metal salt can be composed of organic matter or inorganic matter. As the anion component constituting the organic salt, for example, CH3COO - CF3COO - 、CH3SO3 - CF3SO3 - 、(CF3SO2)3C - 、C4F9SO3 - 、C3F7COO - 、(CF3SO2)(CF3CO)N - , - O3S(CF2)3SO3 - PF6 - 、CO3 2- , anions represented by the following general formulas (1) to (4), etc.

[0116] (1): (C n F 2n+1 SO2)2N - (where n is an integer from 0 to 10),

[0117] (2): CF2(C m F 2m SO2)2N - (wherein m is an integer from 1 to 10),

[0118] (3): - O3S(CF2) l SO3 - (wherein l is an integer from 1 to 10),

[0119] (4): (C p F 2p+1 SO2)N - (C q F 2q+1 SO2) (wherein p and q are integers from 1 to 10).

[0120] In particular, anionic components containing fluorine atoms are preferably used because they can obtain ionic compounds with good ion dissociation properties. As anionic components constituting inorganic salts, Cl - Br - ,I - 、AlCl4 - 、Al2Cl7 - 、BF4 - PF6 - 、ClO4 - 、NO3 - 、AsF6 - 、SbF6 - 、NbF6 - 、TaF6 - 、(CN)2N - As anion component, (CF3SO2)2N is preferred. - 、(C2F5SO2)2N - The (perfluoroalkylsulfonyl)imide represented by the above general formula (1) is particularly preferred, with (CF3SO2)2N - (trifluoromethanesulfonyl)imide as shown.

[0121] Specific examples of organic salts of alkali metals include sodium acetate, sodium alginate, sodium lignin sulfonate, sodium toluene sulfonate, LiCF3SO3, Li(CF3SO2)2N, Li(CF3SO2)2N, Li(C2F5SO2)2N, Li(C4F9SO2)2N, Li(CF3SO2)3C, KO3S(CF2)3SO3K, LiO3S(CF2)3SO3K, etc. Among these, preferred are LiCF3SO3, Li(CF3SO2)2N, Li(C2F5SO2)2N, Li(C4F9SO2)2N, Li(CF3SO2)3C, more preferred are fluorine-containing imide lithium salts in the form of bis(fluorosulfonyl)imide lithium salts such as Li(CF3SO2)2N, Li(C2F5SO2)2N, Li(C4F9SO2)2N, and particularly preferred are (perfluoroalkylsulfonyl)imide lithium salts. Other examples include 4,4,5,5-tetrafluoro-1,3,2-dithiazolidine-1,1,3,3-tetraoxide lithium salt.

[0122] In addition, examples of inorganic salts of alkali metals include lithium perchlorate and lithium iodide.

[0123] <Organic cation-anion salt>

[0124] The organic cation-anion salt used in the present invention is composed of a cation component and an anion component, wherein the cation component is composed of an organic substance. Specific examples of the cation component include: pyridine Cation, piperidine Cation, pyrrolidine Cation, cation having a pyrroline skeleton, cation having a pyrrole skeleton, imidazole Cation, Tetrahydropyrimidine Cations, dihydropyrimidines Cation, pyrazole Cationic, pyrazoline Cations, tetraalkylammonium cations, trialkylsulfonium cations, tetraalkyl Cations, etc.

[0125] As anion components, for example, Cl - Br - ,I - 、AlCl4 - 、Al2Cl7 - 、BF4 - PF6 - 、ClO4 - 、NO3 - 、CH3COO - CF3COO - 、CH3SO3 - CF3SO3- 、(CF3SO2)3C - 、AsF6 - 、SbF6 - 、NbF6 - 、TaF6 - 、(CN)2N - 、C4F9SO3 - 、C3F7COO - 、(CF3SO2)(CF3CO)N - , - O3S(CF2)3SO3 - , anions represented by the following general formulas (1) to (4), etc.

[0126] (1): (C n F 2n+1 SO2)2N - (where n is an integer from 0 to 10),

[0127] (2): CF2(C m F 2m SO2)2N - (wherein m is an integer from 1 to 10),

[0128] (3): - O3S(CF2) l SO3 - (wherein l is an integer from 1 to 10),

[0129] (4): (C p F 2p+1 SO2)N - (C q F 2q+1 SO2) (wherein p and q are integers from 1 to 10).

[0130] Among them, an anion component containing a fluorine atom is particularly preferably used because it can obtain an ionic compound with good ion dissociation property.

[0131] The organic cation-anion salt is preferably selected from a compound composed of the above-mentioned combination of the cation component and the anion component. Preferred specific examples of the organic cation-anion salt include methyl trioctylammonium bis(trifluoromethanesulfonyl)imide, 1-methyl-1-propylpyrrolidine Bis(trifluoromethanesulfonyl)imide, ethylmethylimidazole Among them, 1-methyl-1-propylpyrrolidine is more preferred. Bis(trifluoromethanesulfonyl)imide, ethylmethylimidazole Bis(fluorosulfonyl imide).

[0132] Examples of the ionic compound (B) include inorganic salts such as ammonium chloride, aluminum chloride, cupric chloride, ferrous chloride, ferric chloride, and ammonium sulfate, in addition to the above-mentioned alkali metal salts and organic cation-anion salts.

[0133] In the case where the above-mentioned ionic compound (B) is an alkali metal salt, alkali metal ions such as lithium, sodium, and potassium are cationic components with a molecular weight of less than 210, and therefore, alkali metal salts using these alkali metal ions as cationic components can be appropriately used. In particular, from the viewpoint of compatibility with the adhesive layer, it is preferred that the anion component of the alkali metal salt is an organic salt of an alkali metal composed of an organic substance. In addition, as the above-mentioned alkali metal ion, lithium ions with the smallest molecular weight are preferred. As the above-mentioned ionic compound (B), lithium salts are preferred, and organic salts of lithium are particularly preferred. On the other hand, in the case where the above-mentioned ionic compound (B) is an organic cation-anion salt, an organic cation-anion salt with a molecular weight of less than 210 can be selected from the cationic components exemplified above. From the viewpoint of compatibility with the adhesive layer, organic cation-anion salts whose anion components are composed of organic substances are particularly preferred.

[0134] The proportion of the ionic compound (B) in the adhesive composition of the present invention can be appropriately adjusted so as to satisfy the antistatic properties of the adhesive layer and the sensitivity of the touch panel. For example, it is preferred to consider the type of protective film of the polarizing film, etc., and adjust the proportion of the ionic compound (B) according to the type of liquid crystal panel with built-in touch sensing function so that the surface resistance value of the adhesive layer is 1.0×10 8 ~1.0×10 12 Ω / □ range. For example, Figure 6 In the in-cell type liquid crystal panel with built-in touch sensor function shown in FIG. 1 , it is preferable to control the initial surface resistance value of the adhesive layer to 1×10 8 ~6×10 10 In the range of Ω / □. Figure 7 Semi-embedded type, or Figure 8 In the out-cell type liquid crystal panel with a built-in touch sensor function shown in FIG. 1 , it is preferable to control the initial surface resistance value of the adhesive layer to 1×10 10 ~1×10 12 Ω / □ range.

[0135] When the amount of the above-mentioned ionic compound (B) increases, there is a possibility of precipitation of the ionic compound (B), and humidification peeling is prone to occur. In addition, when the amount of the above-mentioned ionic compound (B) increases, the surface resistance value becomes too low, and there is a hidden danger of reduced sensitivity of the touch panel due to baseline fluctuations (misoperation during touch caused by too low surface resistance value). Relative to 100 parts by weight of (meth) acrylic polymer (A), the proportion of the above-mentioned ionic compound (B) is, for example, usually preferably 40 parts by weight or less, more preferably 20 parts by weight or less, and further preferably 13 parts by weight or less. When it is too little, the antistatic property is poor, and when it is too much, there is concern about reduced touch sensitivity, precipitation of ionic compounds, and deterioration of humidification peeling of adhesives. On the other hand, from the perspective of improving antistatic performance, it is preferred to use more than 0.1 parts by weight of the above-mentioned ionic compound (B). From this point of view, the above-mentioned ionic compound (B) is preferably more than 1 part by weight, more preferably more than 5 parts by weight.

[0136] The adhesive composition of the present invention may contain a crosslinking agent (C). As the crosslinking agent (C), an organic crosslinking agent or a polyfunctional metal chelate may be used. As an organic crosslinking agent, for example, isocyanate crosslinking agents, peroxide crosslinking agents, epoxy crosslinking agents, imine crosslinking agents, etc. may be mentioned. A polyfunctional metal chelate is a chelate obtained by covalently bonding or coordinately bonding a polyvalent metal to an organic compound. As polyvalent metal atoms, Al, Cr, Zr, Co, Cu, Fe, Ni, V, Zn, In, Ca, Mg, Mn, Y, Ce, Sr, Ba, Mo, La, Sn, Ti may be mentioned. As atoms in organic compounds that are covalently bonded or coordinately bonded, oxygen atoms may be mentioned, and as organic compounds, alkyl esters, alcohol compounds, carboxylic acid compounds, ether compounds, ketone compounds, etc. may be mentioned.

[0137] As the crosslinking agent (C), an isocyanate crosslinking agent and / or a peroxide crosslinking agent is preferred.

[0138] As the isocyanate crosslinking agent (C), a compound having at least two isocyanate groups can be used, and for example, known aliphatic polyisocyanates, alicyclic polyisocyanates, aromatic polyisocyanates, etc., which are generally used in urethanization reactions, can be used.

[0139] As the peroxide, any peroxide can be suitably used as long as it generates free radical active species by heating or light irradiation and crosslinks the base polymer of the adhesive composition. However, considering the operability and stability, it is preferred to use a peroxide with a 1-minute half-life temperature of 80°C to 160°C, and more preferably to use a peroxide with a 1-minute half-life temperature of 90°C to 140°C.

[0140] Examples of peroxides that can be used include di(2-ethylhexyl) peroxydicarbonate (1-minute half-life temperature: 90.6° C.), di(4-tert-butylcyclohexyl) peroxydicarbonate (1-minute half-life temperature: 92.1° C.), di-sec-butyl peroxydicarbonate (1-minute half-life temperature: 92.4° C.), tert-butyl peroxyneodecanoate (1-minute half-life temperature: 103.5° C.), tert-hexyl peroxypivalate (1-minute half-life temperature: 109.1° C.), tert-butyl peroxypivalate (1-minute half-life temperature: 110.3° C.), dilauroyl peroxide (1 minute half-life temperature: 116.4℃), dioctanoyl peroxide (1 minute half-life temperature: 117.4℃), 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate (1 minute half-life temperature: 124.3℃), di(4-methylbenzoyl) peroxide (1 minute half-life temperature: 128.2℃), dibenzoyl peroxide (1 minute half-life temperature: 130.0℃), tert-butyl peroxyisobutyrate (1 minute half-life temperature: 136.1℃), 1,1-di(tert-hexylperoxide)cyclohexane (1 minute half-life temperature: 149.2℃). Among them, di(4-tert-butylcyclohexyl) peroxydicarbonate (1 minute half-life temperature: 92.1°C), dilauroyl peroxide (1 minute half-life temperature: 116.4°C), dibenzoyl peroxide (1 minute half-life temperature: 130.0°C), etc. are preferably used because of their particularly excellent cross-linking reaction efficiency.

[0141] The amount of the crosslinking agent (C) used is preferably 3 parts by weight or less, more preferably 0.01 to 3 parts by weight, further preferably 0.02 to 2 parts by weight, and further preferably 0.03 to 1 part by weight relative to 100 parts by weight of the (meth)acrylic polymer (A). It should be noted that when the crosslinking agent (C) is less than 0.01 parts by weight, there is a risk that the crosslinking of the adhesive layer is insufficient and the durability and adhesive properties cannot be satisfied. On the other hand, when it is more than 3 parts by weight, there is a tendency that the adhesive layer becomes too hard and the durability decreases.

[0142] The adhesive composition of the present invention may contain a silane coupling agent (D). By using a silane coupling agent (D), durability can be improved. Specific examples of the silane coupling agent include epoxy group-containing silane coupling agents such as 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; amino group-containing silane coupling agents such as 3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylene)propylamine, and N-phenyl-γ-aminopropyltrimethoxysilane; (meth)acryl group-containing silane coupling agents such as 3-acryloxypropyltrimethoxysilane and 3-methacryloxypropyltriethoxysilane; and isocyanate group-containing silane coupling agents such as 3-isocyanatepropyltriethoxysilane. As the silane coupling agent exemplified above, an epoxy group-containing silane coupling agent is preferable.

[0143] In addition, as a silane coupling agent (D), a silane coupling agent having multiple alkoxysilyl groups in the molecule can also be used. Specifically, for example, X-41-1053, X-41-1059A, X-41-1056, X-41-1805, X-41-1818, X-41-1810, X-40-2651, etc. manufactured by Shin-Etsu Chemical Co., Ltd. can be cited. These silane coupling agents having multiple alkoxysilyl groups in the molecule are not easy to volatilize, and are effective in improving durability due to having multiple alkoxysilyl groups, so they are preferred. In particular, when the adherend of the optical film with an adhesive layer is a transparent conductive layer (such as ITO, etc.) in which the alkoxysilyl group is less reactive than glass, the durability is also suitable. In addition, the silane coupling agent having multiple alkoxysilyl groups in the molecule is preferably one having an epoxy group in the molecule, and more preferably one having multiple epoxy groups in the molecule. Silane coupling agents having multiple alkoxysilyl groups and epoxy groups in the molecule tend to have good durability even when the adherend is a transparent conductive layer (such as ITO, etc.). Specific examples of silane coupling agents having multiple alkoxysilyl groups and epoxy groups in the molecule include X-41-1053, X-41-1059A, and X-41-1056 manufactured by Shin-Etsu Chemical Co., Ltd., and X-41-1056 manufactured by Shin-Etsu Chemical Co., Ltd. having a high epoxy group content is particularly preferred.

[0144] The silane coupling agent (D) may be used alone or in combination of two or more. The total content of the silane coupling agent (D) is preferably 5 parts by weight or less, more preferably 0.001 to 5 parts by weight, further preferably 0.01 to 1 part by weight, further preferably 0.02 to 1 part by weight, and further preferably 0.05 to 0.6 part by weight, based on 100 parts by weight of the (meth)acrylic polymer (A), which is an amount for improving durability.

[0145] In addition, other known additives may be contained in the adhesive composition of the present invention, for example, polyether compounds with reactive silyl groups, polyalkylene glycols such as polypropylene glycol, colorants, pigments and other powders, dyes, surfactants, plasticizers, tackifiers, surface lubricants, leveling agents, softeners, antioxidants, anti-aging agents, light stabilizers, ultraviolet absorbers, inhibitors, inorganic or organic fillers, metal powders, granular, foil-like objects, etc. may be appropriately added according to the intended use. In addition, redox agents that add reducing agents may also be used within a controllable range. These additives are preferably used in an amount of 5 parts by weight or less, more preferably 3 parts by weight or less, and further preferably 1 part by weight or less relative to 100 parts by weight of the (meth) acrylic polymer (A).

[0146] As a method for forming an adhesive layer, the adhesive layer can be prepared by the following methods, for example, the adhesive composition is applied to a separator treated with peeling, etc., and after drying to remove the polymerization solvent, etc. to form an adhesive layer, the adhesive layer is transferred to an optical film (polarizing film); or the adhesive composition is applied to an optical film (polarizing film), and the polymerization solvent is dried to remove the adhesive layer on the optical film, etc. It should be noted that when applying the adhesive, one or more solvents other than the polymerization solvent may be newly added.

[0147] The thickness of the pressure-sensitive adhesive layer is not particularly limited, and is, for example, about 1 to 100 μm, preferably 2 to 50 μm, more preferably 2 to 40 μm, and further preferably 5 to 35 μm.

[0148] From the viewpoint of application to a shaped polarizing film, the creep value of the adhesive layer of the polarizing film with an adhesive layer applied to the present invention at 85°C is preferably 120 μm or less, more preferably 100 μm or less, further preferably 85 μm or less, and particularly preferably 60 μm or less. The lower limit of the above creep value is preferably 15 μm or more, more preferably 30 μm or more. When the above creep value exceeds 120 μm, there is a concern that cracks generated in the shaped polarizing film may worsen as described in the examples. When the creep value is lower than 15 μm, since the stress relaxation property of the adhesive layer becomes lower, there is a concern that the adhesive layer may be easily peeled off during a durability test.

[0149] <Transparent layer>

[0150] The transparent layer will be described in detail below.

[0151] From the viewpoint of thinning and optical reliability, the thickness of the transparent layer is preferably 10 μm or less, more preferably 5 μm or less, further preferably 3 μm or less, further preferably 1.5 μm or less, and further preferably 1 μm or less. When the transparent layer is too thick, the thickness of the polarizing film becomes thicker, and there is a concern that the optical reliability of the polarizer is reduced. On the other hand, from the viewpoint of suppressing the variation ratio of the surface resistance value of the adhesive layer to a relatively small level, the thickness of the transparent layer is preferably 0.1 μm or more, more preferably 0.2 μm or more, and further preferably 0.3 μm or more.

[0152] The material forming the transparent layer can be a material having transparency and capable of suppressing the influence of the adhesive layer on the polarizer. Examples of such a material include a material containing a urethane prepolymer (a) which is a reaction product of an isocyanate compound and a polyol.

[0153] As the isocyanate compound, for example, a polyfunctional isocyanate compound is preferred, and specific examples thereof include polyfunctional aromatic isocyanate compounds, alicyclic isocyanate compounds, aliphatic isocyanate compounds, and dimers thereof.

[0154] Examples of the polyfunctional aromatic isocyanate compound include phenylene diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 2,2′-diphenylmethane diisocyanate, 4,4′-diphenylmethane diisocyanate, 4,4′-toluidine diisocyanate, 4,4′-diphenyl ether diisocyanate, 4,4′-diphenyl diisocyanate, 1,5-naphthalene diisocyanate, xylylene diisocyanate, methylene bis-4-phenyl isocyanate, and p-phenylene diisocyanate.

[0155] Examples of the polyfunctional alicyclic isocyanate compound include 1,3-cyclopentene diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, 1,3-diisocyanate methylcyclohexane, isophorone diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, hydrogenated toluene diisocyanate, and hydrogenated tetramethylxylylene diisocyanate.

[0156] Examples of the polyfunctional aliphatic isocyanate compound include trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,2-propylene diisocyanate, 1,3-butylene diisocyanate, dodecamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate.

[0157] Examples of the polyfunctional isocyanate compound include polyfunctional isocyanate compounds having three or more isocyanate groups, such as tris(6-isocyanatohexyl)isocyanurate.

[0158] Examples of the polyol include ethylene glycol, diethylene glycol, 1,3-butanediol, 1,4-butanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, 2-butyl-2-ethyl-1,3-propanediol, 2,4-diethyl-1,5-pentanediol, 1,2-hexanediol, 1,6-hexanediol, 1,8-octanediol, 1,9-nonanediol, 2-methyl-1,8-octanediol, 1,8-decanediol, octadecanediol, glycerol, trimethylolpropane, pentaerythritol, hexanetriol, and polypropylene glycol.

[0159] As the above-mentioned urethane prepolymer (a), in the present invention, it is preferred to use a rigid structure material in which the proportion of cyclic structures (benzene ring, cyanurate ring, isocyanurate ring, etc.) in the molecular structure is large. For example, the above-mentioned multifunctional isocyanate compound can be used alone or in combination of two or more, but from the viewpoint of inhibiting the mixing of moisture into the above-mentioned polarizer, aromatic isocyanate compounds are preferred. Other multifunctional isocyanate compounds can be used in combination with aromatic isocyanate compounds. In particular, among the aromatic isocyanate compounds, as the above-mentioned isocyanate compound, it is preferred to use at least one selected from toluene diisocyanate and diphenylmethane diisocyanate.

[0160] As the urethane prepolymer (a), trimethylolpropane-tristolyl isocyanate and trimethylolpropane-tris(diphenylmethane diisocyanate) are preferably used. It should be noted that the above-mentioned urethane prepolymer (a) is a compound having a terminal isocyanate group, and can be obtained, for example, by mixing an isocyanate compound with a polyol, stirring, and reacting them. It is usually preferred to mix the isocyanate compound with the polyol in a manner that the isocyanate group is excessive relative to the hydroxyl group of the polyol.

[0161] It should be noted that the above-mentioned urethane prepolymer (a) may also be a urethane prepolymer to which a protective group is imparted to the terminal isocyanate group. As the protective group, there are oxime, lactam, etc. The urethane prepolymer to which the isocyanate group has been protected is heated to dissociate the protective group from the isocyanate group, so that the isocyanate group reacts.

[0162] The material for forming the transparent layer may further contain a compound (b) having at least two functional groups having active hydrogen in addition to the above-mentioned carbamate prepolymer (a), wherein the active hydrogen is reactive with an isocyanate group. Examples of the functional group having active hydrogen reactive with an isocyanate group include a hydroxyl group, an amino group, and the like. The more the number of functional groups having active hydrogen possessed by the above-mentioned compound (b), the more reaction points there are with the isocyanate group of the carbamate prepolymer (a), and the easier it is to form a cured product. Therefore, the number of the above-mentioned functional groups is preferably 3 or more.

[0163] The value obtained by dividing the molecular weight of the compound (b) by the number of functional groups is preferably 350 or less. By defining the relationship between the molecular weight and the number of functional groups, the reactivity of the compound (b) with the isocyanate group of the urethane prepolymer (a) can be ensured.

[0164] The molecular weight of the compound (b) is preferably 1000 or less. The molecular weight of the compound (b) is preferably 1000 or less from the viewpoint of compatibility when preparing a forming material in the form of a solution together with the urethane prepolymer (a).

[0165] Examples of the compound (b) include polyols, polyamines, and compounds having a hydroxyl group and an amino group in the molecule.

[0166] Examples of the polyol include bifunctional alcohols such as ethylene glycol, diethylene glycol, 1,3-butanediol, 1,4-butanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, 2-butyl-2-ethyl-1,3-propanediol, 2,4-diethyl-1,5-pentanediol, 1,2-hexanediol, 1,6-hexanediol, 1,8-octanediol, 1,9-nonanediol, 2-methyl-1,8-octanediol, 1,8-decanediol, octadecanediol, and polypropylene glycol; trifunctional alcohols such as glycerol and trimethylolpropane; tetrafunctional alcohols such as pentaerythritol, hexanetriol, and sorbitol; and alkylene oxide (e.g., propylene oxide) adducts of the above polyols such as polyoxypropylene glycerol ether, polyoxypropylene trimethylolpropane ether, and polyoxypropylene sorbitol ether.

[0167] Examples of the polyamine include ethylenediamine, propylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, isophoronediamine, dicyclohexylmethane-4,4′-diamine, and dimer diamine.

[0168] Examples of the compound having a hydroxyl group and an amino group in the molecule include diamines having a hydroxyl group in the molecule, such as 2-hydroxyethylethylenediamine, 2-hydroxyethylpropylenediamine, di(2-hydroxyethyl)ethylenediamine, di(2-hydroxyethyl)propylenediamine, 2-hydroxypropylethylenediamine, and di(2-hydroxypropyl)ethylenediamine.

[0169] Alkanolamines such as ethanolamine, diethanolamine, triethanolamine, etc.

[0170] From the viewpoint of preventing deterioration in the optical reliability of the polarizer, it is preferred to use a polyol as the compound (b), and trimethylolpropane is particularly preferred from the viewpoint of reactivity with the urethane prepolymer (a).

[0171] The above-mentioned forming material contains the above-mentioned urethane prepolymer (a) as a main component, and preferably contains 50% by weight or more of the urethane prepolymer (a) based on the solid content of the forming material.

[0172] The compound (b) is preferably present in an amount of 5% by weight or more relative to the total of 100% by weight (solid content ratio) of the urethane prepolymer (a) and the compound (b). From the viewpoint of improving film strength, the compound (b) is preferably present in an amount of 10% by weight or more. On the other hand, when the compound (b) is present in an increased amount, the optical reliability of the polarizer may deteriorate. Therefore, the compound (b) is preferably present in an amount of 80% by weight or less, and more preferably in an amount of 50% by weight or less.

[0173] In addition, in order to improve the reactivity of the isocyanate group, a reaction catalyst can be used in the above-mentioned forming material. There is no particular limitation on the reaction catalyst, and a tin catalyst or an amine catalyst is preferred. One or more reaction catalysts can be used. Usually, the amount of the reaction catalyst is 5 parts by weight or less relative to 100 parts by weight of the urethane prepolymer (a). When the amount of the reaction catalyst is large, the crosslinking reaction rate becomes faster, causing foaming of the forming material. Even if the foamed forming material is used, sufficient adhesion cannot be obtained. Usually, when a reaction catalyst is used, it is preferably 0.01 to 5 parts by weight, and more preferably 0.05 to 4 parts by weight.

[0174] In addition, in order to improve the reactivity of the isocyanate group, a reaction catalyst can be used. The reaction catalyst is not particularly limited, and a tin catalyst or an amine catalyst is suitable. One or more reaction catalysts can be used. The amount of the reaction catalyst is usually used in an amount of 5 parts by weight or less relative to 100 parts by weight of the urethane prepolymer. When the amount of the reaction catalyst is large, the crosslinking reaction rate becomes faster, and foaming of the forming material occurs. Even if the forming material after foaming is used, sufficient adhesion cannot be obtained. Usually, when a reaction catalyst is used, it is preferably 0.01 to 5 parts by weight, and more preferably 0.05 to 4 parts by weight.

[0175] As the tin catalyst, any of inorganic and organic ones can be used, but organic ones are preferred. Examples of inorganic tin catalysts include stannous chloride and stannous chloride. Organic tin catalysts are preferably substances having a skeleton such as a methyl group, an ethyl group, an ether group, an ester group, and at least one organic group such as an aliphatic group or an alicyclic group. Examples include tetra-n-butyltin, tri-n-butyltin acetate, n-butyltin trichloride, trimethyltin hydroxide, dimethyltin dichloride, and dibutyltin dilaurate.

[0176] In addition, there is no particular limitation on the amine catalyst. For example, catalysts having at least one organic group such as an alicyclic group such as quinacridone, amidine, and diazabicycloundecene are preferred. In addition, triethylamine and the like can be cited as amine catalysts. In addition, as reaction catalysts other than the above, cobalt naphthenate, benzyltrimethylammonium hydroxide and the like can be cited.

[0177] The above-mentioned forming material is usually used in the form of a solution containing the above-mentioned urethane prepolymer (a) and the above-mentioned compound (b). The solution may be a solvent-based solution or an aqueous solution such as an emulsion, a colloidal dispersion, or an aqueous solution.

[0178] As an organic solvent, there is no particular limitation as long as it does not have a functional group containing active hydrogen that is reactive with an isocyanate group and uniformly dissolves the above-mentioned carbamate prepolymer (a) and the above-mentioned compound (b) constituting the forming material. One organic solvent may be used alone or in combination of two or more. Moreover, the organic solvent may use different solvents for the above-mentioned carbamate prepolymer (a) and the above-mentioned compound (b), respectively. In this case, after preparing each solution, each solution may be mixed to prepare the forming material. In addition, an organic solvent may be further added to the prepared forming material to adjust the viscosity of the forming material. In addition, in the case of a solvent-type solution dissolved in an organic solvent, the following examples of alcohols, water, etc. may also be contained as a solvent.

[0179] Examples of the organic solvent include aromatic hydrocarbons such as toluene and xylene; esters such as ethyl acetate and butyl acetate; aliphatic or alicyclic hydrocarbons such as hexane, cyclohexane, and methylcyclohexane; halogenated alkanes such as 1,2-dichloroethane; ethers such as tert-butyl methyl ether; ketones such as methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, cyclopentanone, and acetylacetone.

[0180] It should be noted that, when it is formed into water-based, alcohols such as n-butanol and isopropanol, ketones such as acetone, etc. can be mixed. When it is formed into water-based, it can be carried out by using a dispersant, or by introducing a functional group with low reactivity with an isocyanate group such as a carboxylate, a sulfonate, a quaternary ammonium salt, or a water-dispersible component such as polyethylene glycol into the urethane prepolymer.

[0181] Examples of the material for forming the transparent layer other than the urethane prepolymer include cyanoacrylate-based materials, epoxy-based materials, and urethane acrylate-based materials.

[0182] The transparent layer can be formed by appropriately selecting the type of the forming material. For example, the transparent layer can be obtained by coating the forming material on a polarizer or the like and then curing it. The transparent layer can be obtained in the form of a coating layer. Usually, the transparent layer is formed by drying at about 30 to 100° C., preferably at 50 to 80° C., for about 0.5 to 15 minutes after the coating, thereby forming a cured layer. In addition, when the forming material contains an isocyanate component, an annealing treatment can be performed at about 30 to 100° C., preferably at 50 to 80° C., for about 0.5 to 24 hours in order to promote the reaction.

[0183] <Image display panel, image display device>

[0184] The polarizing film with an adhesive layer of the present invention can be applied to various image display panels, and the image display panel can be applied to existing image display devices. The other structures in the image display device are the same as those of the existing image display device. As specific examples of image display devices to which the above-mentioned image display panel can be applied, liquid crystal display devices, electroluminescent (EL) displays, plasma displays (PD), field emission displays (FED: Field Emission Display), etc. can be listed.

[0185] The pressure-sensitive adhesive layer-attached polarizing film of the present invention has a small variation ratio in surface resistance value, and is preferably used in a liquid crystal panel with a built-in touch sensor function.

[0186] In addition to the above-mentioned configuration, an optical film such as a retardation film, a viewing angle compensation film, and a brightness enhancement film may be appropriately provided in the liquid crystal panel.

[0187] The liquid crystal layer is not particularly limited, and any type of liquid crystal layer such as TN type, STN type, π type, VA type, IPS type, etc. can be used. The transparent substrate 9 (light source side) is not particularly limited in its raw material as long as it is a transparent substrate, and examples thereof include glass and transparent resin film substrates. Examples of the transparent resin film substrate include those described above.

[0188] For the light source side of the liquid crystal layer, a polarizing film with an adhesive layer conventionally used in the art can be used, and a polarizing film with an adhesive layer described in this specification can also be preferably used.

[0189] A specific example of the above-mentioned liquid crystal panel with built-in touch sensing function is shown in Figure 6 to Figure 8 .exist Figure 6 to Figure 8In the example, the use of the visible side of the liquid crystal cell is shown. Figure 1 The polarizing film 1 with an adhesive layer shown is a polarizing film with an adhesive layer of the present invention. That is, Figure 1 The single-sided protective polarizing film 11 and the adhesive layer 21 are Figure 6 to Figure 8 In the figure, it is shown in the form of a first polarizing film 11 and a first adhesive layer 21.

[0190] Figure 6 It is a so-called embedded type liquid crystal panel with a built-in touch sensing function, which has a structure of first polarizing film 11 / first adhesive layer 21 / first transparent substrate 41 / touch sensor unit 5 / liquid crystal layer 3 / driving electrode and sensor unit 6 / second transparent substrate 42 / second adhesive layer 22 / second polarizing film 12 from the visible side. Figure 6 In an embedded type liquid crystal panel with a built-in touch sensing function, for example, a liquid crystal unit C has a touch sensor portion 5 and a drive electrode and sensor portion 6 in first and second glass substrates 41 and 42 sandwiching a liquid crystal layer 3 (inside the liquid crystal unit).

[0191] in addition, Figure 7 It is a modified example of a so-called embedded type (semi-embedded type) liquid crystal panel with a built-in touch sensing function, which has a structure of first polarizing film 11 / first adhesive layer 21 / touch sensor unit 5 / first transparent substrate 41 / liquid crystal layer 3 / driving electrode and sensor unit 6 / second transparent substrate 42 / second adhesive layer 22 / second polarizing film 12 from the visible side. Figure 7 In an embedded liquid crystal panel with a built-in touch sensing function, for example, the touch sensor portion 5 of the liquid crystal unit C is in direct contact with the first adhesive layer 21 on the outside of the first transparent substrate 41, and has a driving electrode and sensor portion 6 on the side of the second transparent substrate 42 within the first and second glass substrates 41 and 42 (inside the liquid crystal unit) that clamp the liquid crystal layer 3.

[0192] in addition, Figure 8 It is a so-called external embedded type liquid crystal panel with a built-in touch sensing function, which has a structure of first polarizing film 11 / first adhesive layer 21 / touch sensor unit 5 / driving electrode and sensor unit 6 / first transparent substrate 41 / liquid crystal layer 3 / driving electrode 7 / second transparent substrate 42 / second adhesive layer 22 / second polarizing film 12 from the visible side. Figure 8 In an externally embedded liquid crystal panel with a built-in touch sensing function, for example, a liquid crystal unit C has a touch sensor portion 5 and a drive electrode and sensor portion 6 on the outside of a first transparent substrate 41, the touch sensor portion 5 is in direct contact with the first adhesive layer 21, and has a drive electrode 7 on the side of the second transparent substrate 42 inside the first and second glass substrates 41 and 42 (inside the liquid crystal unit) that clamp the liquid crystal layer 3.

[0193] In the liquid crystal panel with built-in touch sensing function, when the touch sensor part 5 of the above-mentioned liquid crystal unit C is in direct contact with the first adhesive layer 21, the antistatic function of the first adhesive layer 21 (containing an ionic compound) is easily reduced, especially in a humidified environment. Therefore, in the above-mentioned example, the liquid crystal panel with built-in touch sensing function of the present invention is suitable for application in Figure 7 The embedded type (variation) shown or Figure 8 The following is an on-cell type LCD panel with built-in touch sensor function.

[0194] It should be noted that the first polarizing film 11 disposed on the visible side of the liquid crystal unit C and the second polarizing film 12 disposed on the opposite side of the visible side can be used after being laminated with other optical films according to the adaptability of their respective configuration positions. As the above-mentioned other optical films, for example, reflective plates, anti-transmission plates, phase difference films (including 1 / 2 wave plates, 1 / 4 wave plates, etc.), visual compensation films, brightness enhancement films, etc., which are optical films as optical layers that are sometimes used in the formation of liquid crystal display devices, etc., can be listed. These other optical films can be used in one layer or two or more layers. When using these other optical films, it is also preferred that the adhesive layer on the side closest to the liquid crystal layer 3 is used as the above-mentioned first adhesive layer 21.

[0195] The liquid crystal layer 3 of the liquid crystal unit C uses a liquid crystal layer suitable for a liquid crystal panel with a built-in touch sensing function, which contains liquid crystal molecules that are uniformly oriented in the absence of an electric field. As the liquid crystal layer 3, it is preferred to use a liquid crystal layer of, for example, an IPS mode. In addition, as the liquid crystal layer 3, any type of liquid crystal layer, such as a TN type, STN type, π type, VA type, etc., can be used. The thickness of the above-mentioned liquid crystal layer is, for example, about 1.5μm to 4μm.

[0196] In the liquid crystal cell C, the first transparent substrate 41 and the second transparent substrate 42 can sandwich the liquid crystal layer 3 to form a liquid crystal cell. According to the form of the liquid crystal panel with a built-in touch sensing function, the touch sensor unit 5, the drive electrode and sensor unit 6, the drive electrode 7, etc. are formed inside or outside the liquid crystal cell. In addition, a color filter substrate can be provided on the liquid crystal cell (the first transparent substrate 41).

[0197] The material forming the transparent substrate may be, for example, glass or a polymer film. Examples of the polymer film include polyethylene terephthalate, polycycloolefin, polycarbonate, etc. When the transparent substrate is formed of glass, its thickness is, for example, about 0.3 mm to 1 mm. When the transparent substrate is formed of a polymer film, its thickness is, for example, about 10 μm to 200 μm. The transparent substrate may have an easy-adhesion layer or a hard coating layer on its surface.

[0198] The touch sensor unit 5 (capacitive sensor), the driving electrode and sensor unit 6, and the driving electrode 7 are formed in the form of a transparent conductive layer. As the constituent material of the above-mentioned transparent conductive layer, there is no particular limitation, and examples thereof include metals such as gold, silver, copper, platinum, palladium, aluminum, nickel, chromium, titanium, iron, cobalt, tin, magnesium, tungsten, and alloys of these metals. In addition, as the constituent material of the above-mentioned transparent conductive layer, metal oxides of indium, tin, zinc, potassium, antimony, zirconium, and cadmium can be listed, and specifically, metal oxides composed of indium oxide, tin oxide, titanium oxide, cadmium oxide, and mixtures thereof can be listed. In addition, other metal compounds composed of copper iodide and the like are used. As needed, the above-mentioned metal oxides may further contain oxides of the metal atoms shown in the above group. For example, it is preferred to use indium oxide (ITO) containing tin oxide, tin oxide containing antimony, and the like, and ITO is particularly preferred. As ITO, it is preferred to contain 80 to 99% by weight of indium oxide and 1 to 20% by weight of tin oxide.

[0199] The position where the touch sensor layer 5 is formed in the liquid crystal cell C is not particularly limited, and the touch sensor layer 5 is formed according to the form of the liquid crystal panel with a built-in touch sensing function. Figure 6 to Figure 8 In the example, the touch sensor layer 5 is arranged between the first polarizing film 11 and the liquid crystal layer 3. The touch sensor layer 5 can be formed in the form of a transparent electrode pattern on the first transparent substrate 41, for example. For the driving electrode and sensor portion 6 and the driving electrode 7, the transparent electrode pattern can also be formed by the usual method according to the form of the liquid crystal panel with a built-in touch sensing function. The above-mentioned transparent electrode pattern is usually electrically connected to a winding (not shown) formed at the end of the transparent substrate, and the above-mentioned winding is connected to the controller IC (not shown). In addition to the comb shape, the shape of the transparent electrode pattern can be any shape such as a stripe shape, a diamond shape, etc. according to the application. The height of the transparent electrode pattern is, for example, 10nm to 100nm, and the width is 0.1mm to 5mm.

[0200] In addition, as the liquid crystal panel with a built-in touch sensor function, a member used to form a liquid crystal display device, such as a member using a backlight or a reflector in a lighting system, can be appropriately adopted.

[0201] Example

[0202] The present invention is specifically described below by manufacturing examples, but the present invention is not limited to these examples. It should be noted that the parts and % in each example are weight basis. The room temperature conditions are 23°C and 65%RH unless otherwise specified.

[0203] <Measurement of Weight Average Molecular Weight of (Meth)Acrylic Polymer (A)>

[0204] The weight average molecular weight (Mw) of the (meth)acrylic polymer (A) was measured by GPC (gel permeation chromatography), and Mw / Mn was measured in the same manner.

[0205] Analytical device: HLC-8120GPC manufactured by Tosoh Corporation

[0206] ·Pillar: Made by Tosoh Corporation, G7000H XL +GMH XL +GMH XL

[0207] · Pillar size: 7.8mmφ×30cm each, total 90cm

[0208] Column temperature: 40℃

[0209] Flow rate: 0.8mL / min

[0210] Injection volume: 100μL

[0211] ·Eluent: Tetrahydrofuran

[0212] Detector: Differential Refractometer (RI)

[0213] Standard sample: polystyrene

[0214] <Production Example 1>

[0215] (Production of 40μm TAC film with HC and 25μm TAC film with HC)

[0216] In a resin solution (manufactured by DIC Corporation, trade name: UNIDIC 17-806, solid content concentration: 80%) obtained by dissolving an ultraviolet curing resin monomer or oligomer having urethane acrylate as the main component in butyl acetate, 5 parts of a photopolymerization initiator (manufactured by BASF Corporation, trade name: IRGACURE 907) and 0.1 parts of a leveling agent (manufactured by DIC Corporation, trade name: GRANDIC PC4100) were added to 100 parts of the solid content in the solution. Then, cyclopentanone and propylene glycol monomethyl ether were added to the above solution at a ratio of 45:55 so that the solid content concentration in the above solution reached 36%, thereby preparing a hard coating forming material. The prepared hard coating forming material was applied to TJ40UL (manufactured by Fuji Film, raw material: cellulose triacetate polymer, thickness: 40 μm) in such a manner that the thickness of the hard coating after curing reached 7 μm, thereby forming a coating film. Then, the coating film was dried at 90°C for 1 minute and further irradiated with a high pressure mercury lamp at a cumulative light intensity of 300 mJ / cm 2 The coating was cured by ultraviolet light to form a hard coating layer (HC), and a 40 μm TAC film with HC was produced.

[0217] Similarly, a hard coat layer (HC) having a thickness of 7 μm was formed on TJ25UL (manufactured by Fuji Film, raw material: cellulose triacetate polymer, thickness: 25 μm) to produce a 25 μm TAC film with HC.

[0218] <Production Example 2>

[0219] (Production of 30 μm acrylic film)

[0220] Into a 30 L kettle reactor equipped with a stirring device, a temperature sensor, a condenser, and a nitrogen inlet pipe, 8000 g of methyl methacrylate (MMA), 2000 g of methyl 2-(hydroxymethyl)acrylate (MHMA), 10000 g of 4-methyl-2-pentanone (methyl isobutyl ketone, MIBK), and 5 g of n-dodecyl mercaptan were added, and the temperature was raised to 105° C. while nitrogen was passed through the reactor. After reflux, 5.0 g of tert-butyl peroxyisopropyl carbonate (Kayakarubon BIC-7, manufactured by Kayaku Akzo) was added as a polymerization initiator, and a solution prepared by 10.0 g of tert-butyl peroxyisopropyl carbonate and 230 g of MIBK was simultaneously added dropwise over 4 hours, and solution polymerization was carried out at about 105 to 120° C. under reflux, and the reaction mixture was aged for 4 hours.

[0221] 30 g of a stearyl phosphate / distearyl phosphate mixture (Phoslex A-18, manufactured by Sakai Chemical Industry Co., Ltd.) was added to the obtained polymer solution, and a cyclocondensation reaction was carried out at about 90 to 120° C. for 5 hours under reflux. Next, the obtained polymer solution was introduced into a vented twin-screw extruder (φ=29.75 mm, L / D=30) having a barrel temperature of 260° C., a rotation speed of 100 rpm, a reduced pressure of 13.3 to 400 hPa (10 to 300 mmHg), one rear vent hole, and four front vent holes at a processing rate of 2.0 kg / h in terms of the amount of resin, and a cyclocondensation reaction and devolatilization were further carried out in the extruder, and extrusion was carried out to obtain transparent pellets of a lactone ring-containing polymer.

[0222] The obtained lactone ring-containing polymer was subjected to dynamic TG measurement, and a mass loss of 0.17 mass % was detected. The lactone ring-containing polymer had a weight average molecular weight of 133,000, a melt flow rate of 6.5 g / 10 min, and a glass transition temperature of 131°C.

[0223] The obtained pellets were kneaded and extruded with acrylonitrile-styrene (AS) resin (ToyoAS AS20, manufactured by Toyo Styrene Co., Ltd.) at a mass ratio of 90 / 10 using a single screw extruder (screw 30 mmφ) to obtain transparent pellets. The obtained pellets had a glass transition temperature of 127°C.

[0224] The pellets were melt-extruded from a 400 mm wide coat hanger T die using a 50 mm φ single screw extruder to produce a 120 μm thick film. The film was stretched to 2.0 times in the longitudinal direction and 2.0 times in the transverse direction at a temperature of 150° C. using a biaxial stretching device to obtain a 30 μm thick stretched film (30 μm acrylic film). The optical properties of the stretched film were measured, and the results showed that the total light transmittance was 93%, the in-plane phase difference Δnd was 0.8 nm, and the thickness direction phase difference Rth was 1.5 nm.

[0225] <Production of polarizing film (1)>

[0226] A polyvinyl alcohol film with a thickness of 45 μm was dyed in an iodine solution with a concentration of 0.3% at 30°C for 1 minute between rollers with different speed ratios, and stretched to 3 times. Then, it was immersed in an aqueous solution containing 4% boric acid and 10% potassium iodide at 60°C for 0.5 minutes, and stretched to a total stretch ratio of 6 times. Next, it was immersed in an aqueous solution containing 1.5% potassium iodide at 30°C for 10 seconds, washed, and then dried at 50°C for 4 minutes to obtain a polarizer with a thickness of 18 μm. Using a polyvinyl alcohol adhesive, a 40 μm TAC film with HC (triacetyl cellulose film side) obtained in Manufacturing Example 1 and subjected to saponification was bonded to one side of the polarizer, and a 30 μm acrylic film obtained in Manufacturing Example 2 was bonded to the other side to produce a polarizing film (1).

[0227] <Production of polarizing film (2)>

[0228] (Manufacturing of Thin Polarizer A)

[0229] A single surface of an amorphous isophthalic acid copolymer polyethylene terephthalate (IPA copolymer PET) film substrate (thickness: 100 μm) having a water absorption of 0.75% and a Tg of 75°C was subjected to corona treatment, and an aqueous solution containing polyvinyl alcohol (degree of polymerization 4200, degree of saponification 99.2 mol%) and acetoacetyl-modified PVA (degree of polymerization 1200, acetoacetyl modification rate 4.6%, degree of saponification of 99.0 mol% or more, manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name "GOHSEFIMER Z200") in a ratio of 9:1 was applied to the corona-treated surface at 25°C and dried to form a PVA-based resin layer with a thickness of 11 μm, thereby producing a laminate.

[0230] The obtained laminate was subjected to free-end uniaxial stretching (auxiliary stretching treatment in gas atmosphere) in which the laminate was stretched to 2.0 times in the longitudinal direction (length direction) between rolls having different peripheral speeds in an oven at 120°C.

[0231] Next, the laminate was immersed in an insolubilization bath (boric acid aqueous solution prepared by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 30° C. for 30 seconds (insolubilization treatment).

[0232] Next, the polarizing plate was immersed in a dyeing solution at a temperature of 30° C. while adjusting the iodine concentration and immersion time so that the polarizing plate reached a given transmittance. In this embodiment, the polarizing plate was immersed in an iodine aqueous solution containing 0.2 parts by weight of iodine and 1.0 parts by weight of potassium iodide per 100 parts by weight of water for 60 seconds (dyeing treatment).

[0233] Next, the sample was immersed in a crosslinking bath (boric acid aqueous solution containing 3 parts by weight of potassium iodide and 3 parts by weight of boric acid per 100 parts by weight of water) at a liquid temperature of 30° C. for 30 seconds (crosslinking treatment).

[0234] Then, the laminate was immersed in an aqueous boric acid solution (an aqueous solution obtained by adding 4 parts by weight of boric acid and 5 parts by weight of potassium iodide to 100 parts by weight of water) at a liquid temperature of 70°C, and uniaxially stretched (stretching treatment in aqueous solution) along the longitudinal direction (length direction) between rollers with different circumferential speeds so that the total stretching ratio reached 5.5 times.

[0235] Then, the laminated body was immersed in a cleaning bath (an aqueous solution prepared by mixing 4 parts by weight of potassium iodide with respect to 100 parts by weight of water) at a liquid temperature of 30° C. (cleaning treatment).

[0236] Through the above operation, an optical film laminate including a polarizer having a thickness of 5 μm was obtained.

[0237] (Manufacturing of adhesives for transparent protective films)

[0238] 45 parts by weight of acryloylmorpholine, 45 parts of 1,9-nonanediol diacrylate, 10 parts of an acrylic oligomer obtained by polymerizing a (meth)acrylic acid monomer (ARUFON UP1190, manufactured by Toagosei Co., Ltd.), 3 parts of a photopolymerization initiator (IRGACURE 907, manufactured by BASF), and 1.5 parts of a polymerization initiator (KAYACURE DETX-S, manufactured by Nippon Kayaku Co., Ltd.) were mixed to prepare an ultraviolet curable adhesive.

[0239] <Production of polarizing film (2)>

[0240] The above-mentioned ultraviolet curing adhesive was applied to the surface of the polarizer A of the above-mentioned optical film laminate so that the thickness of the adhesive layer after curing was 1 μm, and the 25 μm TAC film with HC obtained in the above-mentioned manufacturing example 1 (triacetylcellulose film side) was bonded, and then ultraviolet rays were irradiated as active energy rays to cure the adhesive. For ultraviolet irradiation, a metal halide lamp enclosed in gallium was used, an irradiation device: LightHAMMER10 manufactured by Fusion UV Systems, valve: V valve, maximum illumination: 1600 mW / cm 2 , cumulative exposure 1000 / mJ / cm 2 (wavelength 380-440nm), the illumination of ultraviolet light was measured using the Sola-Check system manufactured by Solatell. Next, the amorphous PET substrate was peeled off and a polarizing film (2) using a thin polarizer was prepared. The optical properties of the obtained polarizing film were: single body transmittance 42.8%, polarization degree 99.99%.

[0241] <Production of polarizing film with transparent layer (2)>

[0242] The following transparent layer forming material was applied to the polarizer surface of the above-mentioned polarizing film (2) (the polarizer surface of the 25μm TAC film with HC was not provided) by a wire bar coater, and then heat treated at 60°C for 12 hours to form a urethane resin layer with a thickness of 3μm, thereby producing a polarizing film (2) with a transparent layer.

[0243] 《Materials for forming the transparent layer》

[0244] As the solution of the urethane prepolymer (a), a 75% ethyl acetate solution of a urethane prepolymer prepared from tolylene diisocyanate (TDI) and trimethylolpropane (TMP) (manufactured by Tosoh Corporation, trade name “Coronate L”) was used.

[0245] On the other hand, trimethylolpropane was dissolved in cyclopentanone so as to have a solid content concentration of 10% to prepare a trimethylolpropane solution.

[0246] The above-mentioned trimethylolpropane solution was added to 100 parts of the above-mentioned 75% ethyl acetate solution of the urethane prepolymer (manufactured by Tosoh Corporation, trade name "Coronate L") so that the solid content ratio of the urethane prepolymer:trimethylolpropane became 90:10, and 0.1 parts of dioctyltin dilaurate catalyst (manufactured by Tokyo Seika Co., Ltd., trade name "EMBILIZER OL-1") was further added, and the solid content concentration was adjusted to 10% using methyl isobutyl ketone as a solvent, thereby preparing a forming material (coating liquid).

[0247] Example 1

[0248] (Preparation of acrylic polymer (A))

[0249] A monomer mixture containing 78.9 parts of butyl acrylate, 16 parts of phenoxyethyl acrylate, 5 parts of acrylic acid, and 0.1 parts of 4-hydroxybutyl acrylate was added to a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube, and a condenser. Furthermore, 0.1 parts of 2,2'-azobisisobutyronitrile as a polymerization initiator and 100 parts of ethyl acetate were added to 100 parts of the above monomer mixture (solid content), and nitrogen was introduced while slowly stirring to replace the nitrogen atmosphere. Then, the liquid temperature in the flask was maintained at about 55°C, and a polymerization reaction was performed for 8 hours to prepare a solution of an acrylic polymer having a weight average molecular weight (Mw) of 2.2 million and Mw / Mn=4.0.

[0250] (Preparation of Adhesive Composition)

[0251] To 100 parts of the solid content of the acrylic polymer solution obtained above, 10 parts of lithium bis(trifluoromethanesulfonyl)imide, 0.6 parts of an isocyanate crosslinking agent (Coronate L manufactured by Tosoh Corporation, trimethylolpropane toluene diisocyanate), 0.1 parts of benzoyl peroxide (NYPER BMT manufactured by NOF Corporation), and 0.3 parts of an epoxy group-containing silane coupling agent (X-41-1056 manufactured by Shin-Etsu Chemical Co., Ltd.) were added to prepare a solution of an acrylic adhesive composition.

[0252] (Production of Polarizing Film with Adhesive Layer)

[0253] Next, the solution of the acrylic adhesive composition was applied to one side of a polyethylene terephthalate film (separator: manufactured by Mitsubishi Chemical Polyester Film Co., Ltd., MRF38) treated with a silicone release agent, and dried at 155° C. for 1 minute to a thickness of 20 μm after drying, thereby forming an adhesive layer on the surface of the separator. Next, the adhesive layer formed on the separator was transferred to the acrylic film side of the polarizing film (1) manufactured above, thereby manufacturing a polarizing film with an adhesive layer.

[0254] Examples 2 to 10, Comparative Examples 1 and 2

[0255] In Example 1, the types and proportions of monomers used in the preparation of the acrylic polymer (A) were changed as shown in Table 1, and the production conditions were controlled to prepare the acrylic polymer (A) solution shown in Table 1.

[0256] In addition, as shown in Table 1, a polarizing film with an adhesive layer was prepared in the same manner as in Example 1 except that the type of polarizing film, the type of ionic compound (B) used in the preparation of the adhesive composition or its blending ratio was changed as shown in Table 1. It should be noted that when the polarizing film (2) was used as the polarizing film, the adhesive layer described in Table 1 was formed on the polarizer surface of the polarizing film (2) (the polarizer surface of the 25 μm TAC film with HC was not provided) in the same manner as above, and when the polarizing film (2) with a transparent layer was used as the polarizing film, the adhesive layer described in Table 1 was formed on the transparent layer of the polarizing film (2) with a transparent layer in the same manner as above.

[0257] The pressure-sensitive adhesive layer-attached polarizing films obtained in the above Examples and Comparative Examples were evaluated as follows. Table 1 shows the evaluation results.

[0258] <Surface resistance value (Ω / □): Conductivity>

[0259] After the separator was peeled off from the pressure-sensitive adhesive layer-attached polarizing film, the surface resistance value of the pressure-sensitive adhesive layer surface was measured as the surface resistance value of the pressure-sensitive adhesive layer-attached polarizing film. The measurement was performed using MCP-HT450 manufactured by Mitsubishi Chemical Analytech Co., Ltd.

[0260] <Determination of creep value>

[0261] The upper end 10mm×10mm of the polarizing film with an adhesive layer (thickness of the adhesive layer: 20μm) cut into a size of 10mm×30mm was adhered to a SUS plate through the adhesive layer, and an autoclave treatment was performed for 15 minutes at 50°C and 5 atmospheres. A precision hot plate set in a vertical manner with the heating surface was heated to 85°C, and the SUS plate with the polarizing film with the adhesive layer was set in such a way that the side without the adhesive layer was in contact with the heating surface of the hot plate. After heating the SUS plate at 85°C for 5 minutes, a load of 500g was applied to the lower end of the polarizing film with the adhesive layer, and the offset amplitude of the polarizing film with the adhesive layer and the SUS plate before and after the load was applied after being placed for 1 hour was measured, and the offset amplitude was taken as the creep value (μm) at 85°C.

[0262] <Durability test>

[0263] The prepared polarizing film with an adhesive layer was cut into a size of 300×220 mm in such a way that the absorption axis of the polarizing film was parallel to the long side. The polarizing film with an adhesive layer was bonded to a 350×250mm×0.7mm thick alkali-free glass (manufactured by Corning, trade name "EG-XG") using a laminator. Next, an autoclave treatment was performed at 50°C and 0.5MPa for 15 minutes to make the adhesive layer adhere to the glass. After the sample subjected to the treatment was treated in an atmosphere of 85°C for 500 hours and in an atmosphere of 60°C / 95%RH for 500 hours, the appearance of the sample was evaluated by visual observation according to the following criteria.

[0264] (Evaluation Criteria)

[0265] A: There is absolutely no change in appearance such as foaming or peeling.

[0266] B: There is slight peeling or foaming at the end, but there is no problem in practical use.

[0267] C: There is peeling or foaming at the edge, but there is no problem in practical use unless it is for special purposes.

[0268] D: There is significant peeling at the edge, which is problematic in practical use.

[0269] <ESD test>

[0270] After the separator was peeled off from the polarizing film with the adhesive layer, it was bonded to the visible side of the in-cell liquid crystal unit to produce a liquid crystal panel with a built-in touch sensor function. Figure 6 The first transparent substrate of the embedded liquid crystal unit shown in the figure formed a first adhesive layer and a first polarizing film. The polarizing film in the liquid crystal panel was subjected to an ESD (electrostatic discharge) gun (10 kV) to measure the time until the white spots caused by electricity disappeared, and the evaluation was made according to the following criteria.

[0271] (Evaluation Criteria)

[0272] A: Within 1 second

[0273] B: More than 1 second and less than 10 seconds

[0274] C: More than 10 seconds

[0275] <Evaluation of irregular cracks>

[0276] The prepared polarizing film with an adhesive layer was processed using a CO2 laser processing machine Spirit (manufactured by GCC, 30W) at a speed of 10, a laser output of 35, and 400 ppi. Figure 5 Shape shown.

[0277] The profiled polarizing film with adhesive layer was bonded to 350mm×250mm×0.7mm thick alkali-free glass (Corning, trade name "EG-XG"), and then autoclaved at 50°C and 0.5MPa for 15 minutes to make the adhesive layer adhere to the glass. The sample after this treatment was put into a heating cycle test tank, and the presence or absence of cracks generated in the profiled part at the time of 100 cycles and 200 cycles was confirmed by naked eye observation. Five identical samples were put in under each condition, and the number of samples with cracks is recorded in Table 1.

[0278] (Test conditions)

[0279] Temperature conditions: -40°C (maintain for 30 minutes) 85℃ (30 minutes hold) as a cycle and repeated, and its heating / cooling rate: 10℃ / min

[0280] <Evaluation of end discoloration>

[0281] The single-side protected (or double-side protected) polarizing film with adhesive layer obtained in the examples and comparative examples was cut into 50 mm × 50 mm, and after peeling off the diaphragm, it was bonded to 1.2-1.5 mm thick alkali glass (manufactured by Matsunami Glass Co., Ltd., microscope slide) through the adhesive layer to prepare a sample. After the sample was kept in a high temperature and high humidity environment of 60°C and 90% RH for 500 hours, the end discoloration amount was measured under the following conditions using a differential interference microscope (manufactured by Olympus, product name "MX-61L"). The end discoloration amount is measured as follows: the distance between the position closest to the center of the diagonal line of the four corners of the sample, where the color becomes lighter than the center, and the straight line connecting the corners is set as the end discoloration amount (μm), and the average value of the four corners is set as the end discoloration amount of the sample.

[0282] Device: Olympus MX-61L

[0283] Measurement conditions

[0284] Lens magnification: 5 times

[0285] ISO: 200

[0286] Shutter speed: 1 / 100

[0287] Reflected light: 0 scale

[0288] White balance: Automatic

[0289] Transmitted light controller: LG-PS2

[0290] Transmitted light: 5 scales

[0291] Polarization direction of transmitted light: Orthogonal to Nicol's direction relative to the transmission axis of the polarizing film

[0292]

[0293] In Table 1,

[0294] BA represents butyl acrylate,

[0295] PEA stands for phenoxyethyl acrylate,

[0296] AA stands for acrylic acid,

[0297] NVP stands for N-vinyl-2-pyrrolidone,

[0298] HBA represents 4-hydroxybutyl acrylate,

[0299] Isocyanates represent isocyanate crosslinking agents (Coronate L manufactured by Tosoh Corporation, trimethylolpropane toluene diisocyanate),

[0300] BPO represents benzoyl peroxide (NYPER BMT manufactured by NOF Corporation),

[0301] Li-TFSI represents lithium bis(trifluoromethanesulfonyl)imide,

[0302] K-TFSI represents potassium bis(trifluoromethanesulfonyl)imide,

[0303] TMPA-TFSI represents trimethylpropylammonium bis(trifluoromethanesulfonyl)imide salt,

[0304] EMP-TFSI stands for ethylmethylpyrrolidine Bis(trifluoromethanesulfonyl)imide salt,

[0305] TBMA-TFSI represents tributylmethylammonium bis(fluoromethanesulfonyl)imide salt,

[0306] MTOA-TFSI stands for methyltrioctylammonium bis(trifluoromethanesulfonyl)imide salt.

Claims

1. A polarizing film with an adhesive layer, comprising a polarizing film and an adhesive layer, wherein the polarizing film comprises a polarizer and a protective film disposed on one or both sides of the polarizer, The polarizing film with an adhesive layer has a non-rectangular shaped portion, The pressure-sensitive adhesive layer is formed from a pressure-sensitive adhesive composition containing a (meth)acrylic polymer (A) and an ionic compound (B) having a molecular weight of 210 or less as a cationic component.

2. The polarizing film with an adhesive layer according to claim 1, wherein The cationic component is a lithium ion.

3. The polarizing film with an adhesive layer according to claim 1, wherein The ionic compound (B) is contained in an amount of 0.1 to 13 parts by weight based on 100 parts by weight of the (meth)acrylic polymer (A).

4. The polarizing film with an adhesive layer according to claim 1, wherein The protective film is any one selected from a cellulose resin film and a (meth)acrylic resin film.

5. The polarizing film with an adhesive layer according to claim 1, wherein The thickness of the polarizer is less than 10 μm.

6. The polarizing film with an adhesive layer according to claim 1, wherein The polarizing film is a single-side protective polarizing film including a polarizer and a protective film provided only on one side of the polarizer.

7. The polarizing film with an adhesive layer according to claim 6, wherein The other side of the polarizer in the single-sided protective polarizing film has the adhesive layer.

8. The polarizing film with an adhesive layer according to claim 7, wherein The other surface of the polarizer in the one-side protective polarizing film has the pressure-sensitive adhesive layer via a transparent layer having a thickness of 10 μm or less and formed directly on the polarizer.

9. The polarizing film with an adhesive layer according to claim 8, wherein The transparent layer is a cured product of a forming material containing a urethane prepolymer, and the urethane prepolymer is a reaction product of an isocyanate compound and a polyol. 10 . The pressure-sensitive adhesive layer-attached polarizing film according to claim 1 , wherein: The adhesive layer has a creep value of 120 μm or less at 85° C. 11 . An image display panel comprising the pressure-sensitive adhesive layer-attached polarizing film according to claim 1 .

12. The image display panel according to claim 11, wherein: The pressure-sensitive adhesive layer of the pressure-sensitive adhesive layer-attached polarizing film is bonded to a liquid crystal cell with a built-in touch sensing function that includes a liquid crystal layer and a touch sensor portion. 13 . An image display device comprising the image display panel according to claim 11 .

Citation Information

Patent Citations

  • Production and use of clear heat-resistant resin

    JP2000230016A

  • Method of manufacturing for transparent heat resistant resin and use of the same

    JP2001151814A

  • Transparent thermoplastic resin laminate

    JP2002120326A

  • Thermoplastic resin laminate

    JP2002254544A

  • Lactone ring-containing polymer, and its manufacturing method and application

    JP2005146084A